Identifying common mutations in colorectal cancer using a 7-gene panel by next generation sequencing - Chai, Boon Lee; Yip, Wai Kien; Mohd Dusa, Noraini; Mohtarrudin, Norhafizah; Seow, Heng Fong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Colorectal cancer (CRC) arises from the cumulative effects of genetic and epigenetic alterations. Cur-rent treatment of metastatic CRC relies on combination of chemotherapy and targeted therapies such as anti-EGFR therapies. The success of targeted therapies relies on the detection of actionable targets and predictive biomarkers of resistance. The study aims to determine mutations in common actionable targets and predictive biomarkers of resistance to anti-EGFR therapies in Malaysian CRC patients. Methods: Mutations in 10 CRC tissues were determined by next-generation sequencing with a panel of 7 cancer-related genes covering all exons in KRAS, BRAF, PIK3CA, PTEN, TP53, NRAS, and EGFR genes. Immunohistochemistry was used to determine mismatch repair (MMR) status. Results: Of the ten samples, 5 and 4 samples harboured two and one mutation, respectively and one had no mutation. All were missense mutations and were in five genes, namely, KRAS, PIK3CA, TP53, BRAF, and EGFR. They were, G12D, G12V, G12A, G13D, and V14I in KRAS, E545K, K733R, and D1056N in PIK3CA, G199V, D259Y, and R282W in TP53, V600E in BRAF and G696R in EGFR. Deficient mismatch repair (dMMR) was detected in three samples, of which two had KRAS mutation. Conclusion: Mutations in KRAS codon 12 and 13, BRAF and PIK3CAwhich predict resistance to anti-EGFR therapies and three TP53 mutations were found. This is the first report of EGFR mutation in Malaysian CRC patients. It is predicted to be a pathogenic variant. dMMR, one of the biomarkers for treatment with immune checkpoint inhibitor was also detected.